Artificial Intelligence in Education: Analysis and Assessment of Legal Knowledge Using AI Tools - Anvar J. Khurramov; Mavluda A. Axmedshaeva; Fiyuza A. Mukhitdinova; Gulnora A. Xudayberdiyeva; Shahnoza S. Almosova; Makhmud M. Makhamatov; Sherzod R. Khayitov (Qubahan Academic Journal)
This study explores the ethical and legal implications of integrating artificial intelligence (AI) into science and mathematics education, with a specific focus on legal pedagogy in the Central Asian context. The primary aim is to analyses how AI technologies intersect with existing educational and legal frameworks and to investigate the perceptions of educators and students regarding AI's use in academic environments. The research addresses a notable gap in global literature by incorporating perspectives from Uzbekistan, Kazakhstan, and Kyrgyzstan—regions often underrepresented in AI and education discourse. A mixed-methods approach was employed, combining a structured questionnaire distributed to 341 participants and a qualitative assessment of open-ended responses. The study examined ethical concerns such as algorithmic bias, transparency, and student privacy, as well as legal dimensions related to consent, data protection, and institutional responsibility. AI tools used in legal education were evaluated through both user experience and pedagogical effectiveness, and results were categorized based on demographic variables such as age, gender, occupation, and prior AI exposure. Findings reveal substantial optimism toward AI's capacity to personalize learning and enhance analytical thinking, though participants expressed strong concerns about ethical oversight, legal ambiguity, and unequal access to technology. The study's significance lies in its contextual specificity and the development of a regionally grounded framework for ethical AI deployment in education. Recommendations include clear institutional guidelines, targeted teacher training, and the adoption of AI systems that align with legal norms and moral standards in education. The study contributes a practical roadmap for policymakers and educators navigating AI adoption within diverse legal traditions.